Pattern matching technique from B-rep model - Saaid, S. S.; Ismail, Napsiah; Wong, Shaw Voon; Sulaiman, Shamsuddin; Osman, Mohd. Rasid (2005)
Feature recognition is one of the automatic input identification for Computer Aided Manufacturing (CAM) application such as process planning, part programming and inspection planning. Feature recognition techniques for Computer-Aided Design (CAD) have been widely researched in recent years with most of the effort being focused on feature recognition for machining application. This paper describes the pattern matching technique for recognizing part features from B-Rep. This technique uses standard for the exchange of product information (STEP) formats for geometrical data extraction. The advantages and disadvantages of pattern matching technique are also discussed.